Anti-Interleukin 5 (IL-5) and IL-5Ra Biological Drugs: Efficacy, Safety, and Future Perspectives in Severe Eosinophilic Asthma - Bagnasco, Diego; Ferrando, Matteo; Varricchi, Gilda; Puggioni, Francesca; Passalacqua, Giovanni; Canonica, Giorgio Walter (Frontiers in Medicine, 2017)
The definition of asthma has profoundly changed in recent years, thus recognizing that asthma itself is not a single disease but a heterogeneous disorder that includes different phenotypes and, possibly, endotypes. A more detailed knowledge of the immunological mechanisms of the asthma pathogenesis has enabled identifying interleukin 5 (IL-5) as a crucial cytokine in several asthma phenotypes. IL-5, in fact, exerts selective action on eosinophils which, in turn, sustain airway inflammation and worsen asthma symptoms and control. The development of drugs targeting IL-5 or its receptor alpha subunit (IL-5Rα) has been shown, in clinical trials, a promising different therapeutic approach to a problematic type of asthma, the severe one, whose characteristics make the patient not controlled by normal therapies and , until today, only partially controlled by means of systemic steroid therapy with its well-known side-effects or by Omalizumab in the allergic subtypes. Beginning with the design process of clinical trials, the importance of patient selection was immediately identified, taking into account both medical records, such as exacerbations, lung function and quality of life, and biomarkers like eosinophils that were predictive of therapeutic responses